Citra Destinasi terhadap Kepuasan Pengunjung dan Niat Rekomendasi - Nuraini Khusnul Khotimah; Rita Indah Mustikowati; Iva Nurdiana Nurfarida; Mohammad fakhruddin mudzakkir (Program Studi Manajemen Fakultas Ekonomi Universitas Samudra, 2023)
This study focuses on studying how the image of a destination from tourists that appears is related to tourist satisfaction and subsequently has the intention to recommend the place to others. Destination imagery is studied through three components – cognitive, affective, and unique. Findings from 170 samples through surveys and distributing questionnaires both online and offline to visitors to Batu City tourism objects which are then processed using the SEM-pls 3.0 method. The results reveal that affective image affects tourist satisfaction and post-visit behavior; the cognitive component had a significant effect on all constructs, except recommendation intentions, while unique image also affected tourist satisfaction and post-visit behavior.